RELASI KUASA ANTARA PEMODAL DENGAN PETANI SAYUR DALAM PENGELOLAAN PERTANIAN DI DESA PENGADANGAN KECAMATAN PRINGGASELA KABUPATEN LOMBOK TIMUR - Waiz Nadia Rahmatin (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2020)
Power relations is a social structure of society that has a diverse pattern of relationships within a society that can interact with each other according to certain relationship patterns. The power relation creates interdependence between various parties starting from those who hold power and those who are the object of power. This research is located in the Village District of Pringgasela District with research subjects investors, vegetable farmers and rural communities, how power relations between investors and vegetable farmers in agricultural management. Subject determination technique by purposive sampling. The research method used is descriptive qualitative, data collection techniques carried out by observation, interviews, and documentation. With data analysis using qualitative. The results showed that the power relations that occurred between investors and vegetable farmers were indeed true because in the management of agriculture the position of the farmers was greatly disadvantaged while the farmers depended on investors. While the positive impact is interdependence in life. The negative impact is that vegetable farmers do not have power over investors because investors here have full power over vegetable farmers.